Comparative evaluation of proximate compositions and taste attributes of three Asian hard clams (Meretrix meretrix) with different shell colors. Issue 1 (1st January 2020) - Wen, Xinyi; Chen, Aihua; Wu, Yangping; Yang, Yunyi; Xu, Yanshun; Xia, Wenshui; Zhang, Yu; Cao, Yi; Chen, Suhua
ABSTRACT: Meretrix meretrix with three shell colors (mottled shell, red shell, yellow shell) were analyzed for nutritive and taste attributes. Additionally, the influence of cooking on the taste active components was also evaluated. The three kinds of clams had higher crude protein contents. Alanine, glutamic acid, arginine, 5ʹ-adenosine monophosphate, Cl −, Na +, K + and PO4 3- were the major taste compounds of Meretrix meretrix . In addition to PO4 3-, the contents of all major taste compounds decreased after cooking. Among raw samples, red shell clams had the highest value of equivalent umami concentration (EUC) and contents of Cl − and Na +, along with the lowest content of PO4 3- . In cooked samples, the value of EUC and the contents of Na + and K + in red shell clams were higher than those of yellow shell clams and lower than those of mottled shell clams. Furthermore, the contents of PO4 3- in red and yellow shell clams were higher than that in mottled shell clams. However, there were no significant differences in the amount of K + among different raw samples and the amount of Cl − among different cooked samples.